Analysis of major errors in the design of pumping stations and manure storage on pig farms - Boltianskyi, Oleh; Boltianskyi, Borys; Boltianska, Natalia; Болтянский, Олег Владимирович; Болтянский, Борис Владимирович; Болтянская, Наталья Ивановна (My University, 2016)
EA: We consider the manure removal system, which is used in most pig farms being built and reconstructed at present in Ukraine, and it has been discovered that there are major mistakes during the baths construction in the correct geometry and depth, and therefore discusses their rules of operation. If the baths geometry is wrongly executed, for instance, if the slope is made to slant toward the bottom of the tub filler drain pipe, which in itself is unacceptable, or not properly executed in the form of a special pit steps towards the neck drain, and etc., then a number of problems is inherent of its exploitation. The basic requirements for laying fused-pipe is compliance with its slope. The considered equipment must be equipped with pumping stations to pump manure. The pumps for pumping manure: submersible sewage pumps and dryinstalled in the mine and long sewage pumps with electric or PTO shaft of a tractor were analyzed. Attention was paid to the designing of modern equipment for the distribution of manure waste into fractions. The classification of manure storage and the basic requirements for their placement and arrangement was carried out, and recommendations are made for the designing of pumping stations, to select pumps for the pumping stations and the design during the modern construction and reconstruction of old pig farms. RU: Рассмотрена система удаления гноя, что применяется на большинстве свинокомплексов, что строятся и реконструируются на данное время в Украине, основные ошибки при строительстве ванн относительно их правильной геометрии и глубины и рассмотрены правила их эксплуатации. В случае если геометрия ванны выполнена неправильно - например сделанный уклон дна ванны в сторону горловины сливной трубы, что сам по себе является недопустимым; не выполнен специальный приямок в виде ступеньки перед сливной горловиной и др., то при эксплуатации ванн возникает ряд проблем. Определены основные требования к прокладке самосплавной трубы с соблюдением ее уклона. Рассмотрено оборудование, которым должны оснащаться насосные станции для перекачивания навоза. Приведен анализ насосов для перекачивания навоза: погружные фекальные насосы, насосы сухой установки в шахте и довговальные фекальные насосы с электроприводом или приводом от вала отбора мощности трактора. Уделено внимание современному оборудованию для разделения стоков навоза на фракции. Приведена классификация навозохранилищ и основные требования к их размещению и обустройству. Рассмотрены основные ошибки и сформулированы рекомендации при проектировании насосных станций, подборе насосов для насосных станций и проектировании навозонакопителей во время строительства современных и реконструкции старых свинокомплексов.
Анализ основных ошибок при проектировании насосных станций и хранении навоза на свинофермах
Keywords: свиноводство; удаление навоза; утилизация навоза; насосные станции; навозохранилища; рig manure; manure disposal; pumping stations; manure storage